2007
DOI: 10.1213/01.ane.0000263270.39480.a2
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Amplifies Pain Responses to Uterine Cervical Distension in Rats by Altering Transient Receptor Potential-1 Function

Abstract: These data suggest that the TRPV-1 channel is unimportant for normal mechanosensation in the cervix in the absence of estrogen, since capsaizepine failed to reduce responses to uterine cervical distension in rats without estrogen replacement. In contrast, TRPV-1 function is important for estrogen-induced sensitization. These data raise the possibility that acute and chronic pain coming from the cervix, such as labor or cancer, may be enhanced by estrogen and might be reduced by antagonists of TRPV-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 19 publications
0
40
1
1
Order By: Relevance
“…24 -26 Moreover, such complicated communication in the nervous system may also underlie the pathophysiologic mechanisms of viscero-visceral referred pain, which is manifested as injury or inflammation in one pelvic organ leading to modifications in others. [27][28][29][30] By instilling capsaicin into the descending colon, we demonstrated that activation of nociceptive afferent fibers in the descending colon sensitized urethra reflex activity in a cross-organ manner. This cross-organ reflex sensitization might, at least in part, mimic the pathophysiologic conditions that occur during acute colon irritation.…”
Section: Discussionmentioning
confidence: 89%
“…24 -26 Moreover, such complicated communication in the nervous system may also underlie the pathophysiologic mechanisms of viscero-visceral referred pain, which is manifested as injury or inflammation in one pelvic organ leading to modifications in others. [27][28][29][30] By instilling capsaicin into the descending colon, we demonstrated that activation of nociceptive afferent fibers in the descending colon sensitized urethra reflex activity in a cross-organ manner. This cross-organ reflex sensitization might, at least in part, mimic the pathophysiologic conditions that occur during acute colon irritation.…”
Section: Discussionmentioning
confidence: 89%
“…Except being essential for urethral closure, pathological overactivation of the neural substrate involved in the pelvicurethra reflex activity caused by injury or inflammation may produce urethra hypereflexia or detrusor-sphincter dys-synergia (28), which are seen in patients with lower urinary tract syndrome (74,79). Therefore, whether the blockage of descending facilitation on the SRP and urethra activity caused by WAY-100653 also implied that spinal serotonergic 5-HT 1A receptors can be substantial candidates to relieve the neurogenic hyperactive or dys-synergic urethra in patients with lower urinary tract syndrome (20,72) is an interesting topic to be investigated further.…”
Section: Discussionmentioning
confidence: 99%
“…En este sentido, se ha publicado que la anandamina, que induce vasodilatació n en la vasculatura mesenté rica de ratas Sprague-Dawley, aumenta la expresió n de TRPV1 en las aferencias de cuello uterino en ratas amplificando la respuesta a estímulos dolorosos 31 .…”
Section: Discusió Nunclassified